Opportunities and Prospects of Developing Tourist Industry Infrastructure in the Republic of Altay on the Basis of State-Private Partnership - M. I. Razuvaeva (Вестник Российского экономического университета имени Г. В. Плеханова)
The research deals with planning and developing tourist industry in the Republic of Altay on the basis of mechanisms of state-private partnership oriented to building the necessary tourist infrastructure in the region. In the research the author analyzed trends in developing the system of academic views and regulatory control of stateprivate partnership in the Russian Federation and systematized key forms of direct and indirect participation of state in the face of bodies of state governance and regional levels in implementation of investment projects with cornerstone impact on social and economic and technological development of territories. The author checked tourist potential of the Republic of Altay and sufficiency of tourist infrastructure units in the region according to strategy of social and economic development of the region. Apart from that, the article identified technological and operation features of building and using different units of tourist infrastructure in the region and worked out recommendations aimed at application of concrete forms and methods of state-private partnership in order to ensure the complex development of tourist infrastructure in the Republic of Altay. Findings of the research can be used for elaboration and realization of the Republic of Altay policy aimed at tourism development in the region.